2004
DOI: 10.1021/ie049661l
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatics of the Granular Flow in a Pneumatic Conveying System

Abstract: The phenomenon of electrostatic charge generation and its effects on granular flow behavior in a pneumatic conveying system was studied. The main parameters used for quantitative characterization of the phenomenon were the induced current, particle charge density, and equivalent current of the charged granular flow. These were measured using a digital electrometer, Faraday cage, and modular parametric current transformer, respectively. Three different flow patterns corresponding to different electrostatic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 21 publications
(35 reference statements)
14
96
0
Order By: Relevance
“…They found that granular cluster pattern differs with the voltage set [12][13][14] and is affected by humidity. 15 A similar phenomenon was observed 2 for larger particles (2.8mm) where three characteristic aggregation patterns (clusters, half-ring, and ring) were formed in a vertical pipe due to electrostatic effects in a pneumatic conveying system. Al-Adel et al 16 investigated the effect of static electrification on gas-solid flows in vertical risers and captured qualitative features of riser flows: core-annular particle distribution, annular particle downflow at low riser gas velocities, and annular upflow at high gas velocities.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…They found that granular cluster pattern differs with the voltage set [12][13][14] and is affected by humidity. 15 A similar phenomenon was observed 2 for larger particles (2.8mm) where three characteristic aggregation patterns (clusters, half-ring, and ring) were formed in a vertical pipe due to electrostatic effects in a pneumatic conveying system. Al-Adel et al 16 investigated the effect of static electrification on gas-solid flows in vertical risers and captured qualitative features of riser flows: core-annular particle distribution, annular particle downflow at low riser gas velocities, and annular upflow at high gas velocities.…”
Section: Introductionsupporting
confidence: 65%
“…Based on previous triboelectrification experiments in the pneumatic conveying system using PP granules and PVC pipes, 2,25 it can be deduced that positive charges are generated on the PP granule surface while equal amounts of negative charges are accumulated on the PVC pipe wall (Figure 2c). In the pipe cross section with grid level 20 ϫ 40 (Figure 2a), the electrostatic field vector (Figure 2d) at the point (i,j) from the point charge (l, k) can be calculated by the following:…”
Section: Electrostatic Fieldmentioning
confidence: 79%
See 3 more Smart Citations